The influence of adiponectin on carbohydrates, lipids, and lipoproteins metabolism: analysis of signaling mechanisms - D. A. Tanyanskiy; A. D. Denisenko (Ожирение и метаболизм, 2021)
Dysregulation of adipose tissue functions makes a significant contribution to the pathogenesis of metabolic syndrome, one of the most common diseases in recent years. Adipose tissue is an organ that secretes at least several dozen signaling molecules, adipokines. One of the most studied and at the same time mysterious adipokines is adiponectin. The latter is due to the lack of clear ideas about the biological role of this adipokine, the presence of its several molecular forms with different activity and several types of receptors to this adipokine localized in almost all cells of the body. The purpose of this review is to summarize and analyze the available information about the molecular mechanisms of the effect of adiponectin on metabolism of carbohydrates, lipids and lipoproteins. The literature search was conducted by the keywords "adiponectin" and "metabolic syndrome" in the Pubmed and Elibrary.ru databases for the period from 1995 to 2021.According to the results of the literature analysis, it is assumed that adiponectin is involved in energy metabolism as a «satiety» hormone that promotes the utilization and storage of energy-rich substrates, fatty acids and glucose, which prevents the development or mitigates the already developed insulin resistance. This reduces the amount of plasma triglycerides and increases the level of high-density lipoproteins in the plasma. Adiponectin affects metabolic processes by activating the AdipoR1-APPL1-LKB1-AMPK, AdipoR1-APPL1-p38, AdipoR2-PPARa cascades, and possibly by activating the ceramidase and phosphoinositide pathways and insulin signaling. In addition to the AdipoR1/2 receptors, the adhesion molecule T-cadherin may be involved in the transduction of the adiponectin signal in endothelial and muscle cells. The mechanisms of signal transduction from T-cadherin, as well as from AdipoR2, remain unclear. Studies on the mechanisms of the action of individual molecular forms of adiponectin are extremely rare. The analysis shows the complex nature of adiponectin signaling, many of the mechanisms of  which remain undiscovered, and it is possible that the near future will bring us significant progress in this area.